Analisis Perkembangan Peserta Didik Usia Sekolah Dasar (8-9 Tahun) Ditinjau dari Aspek Fisik, Kognitif, Emosional, Sosial, Moral, dan Spiritual - Nuri Alfitriyani; Zaura Izzati Siagian; Khairina Habib Rangkuti; Elvira Zahratunnisa; Ramadan Lubis (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
This study aims to analyze the development of elementary school students (ages 8–9) in terms of physical, cognitive, emotional, social, moral, and spiritual aspects. The research subjects were two third-grade students named Dinul Mumtaz (8 years old) and Alfatir Ramadhan Hendri (9 years old). This study used a qualitative approach, with observation and interviews as the main data collection techniques. The results indicate that both students show physical development appropriate for their age, with well-developed fine and gross motor skills. In the cognitive aspect, both have reached the concrete operational stage, characterized by logical thinking, understanding of cause-and-effect relationships, and the ability to solve tasks using concrete objects. In terms of emotional and social development, Dinul and Alfatir demonstrate the ability to recognize and manage emotions, as well as build positive social relationships with peers and teachers. Moral development shows that both students are in the heteronomous and early conventional stages, where they obey rules due to authority and a desire to gain social approval. Meanwhile, in the spiritual aspect, both students demonstrate good religious habits and an understanding of spiritual values reflected in their daily behavior. Therefore, it can be concluded that the development of both students is in a good category and in accordance with child development theories, supported by positive influences from family and school environments.